PENGARUH GAYA KEPEMIMPINAN, DISIPLIN KERJA DAN KOMPENSASI TERHADAP KINERJA MELALUI KEPUASAN KERJA SEBAGAI VARIABEL INTERVENING PADA ASN BADAN PENDAPATAN DAERAH KABUPATEN SITUBONDO - Hotimah, Husnul; Soeliha, Siti; Pramesthi, Riska Ayu (Fakultas Ekonomi dan Bisnis, 2024)
The Regional Revenue Agency is a local government organization responsible for regulating and managing local taxes and remuneration. The target population for this study consisted of 40 state civil apparatus members from the Regional Revenue Agency in Situbondo district. The sample was selected using simple random sampling. Data analysis and hypothesis testing were conducted using the Structural Equation Model – Partial Least Square (PLS-SEM) method. The study focuses on examining the influence of leadership style, work discipline, and compensation on performance, with job satisfaction serving as an intervening variable. The results of the direct influence hypothesis test using the Smart PLS 3.0 application show that leadership style has a significant positive influence on job satisfaction, work discipline has a negative but not significant influence on job satisfaction, compensation has a negative but not significant influence on job satisfaction, leadership style has a significant negative influence on performance, work discipline has a positive but not significant influence on performance, compensation has a positive but not significant influence on performance, and job satisfaction has a significant positive influence on performance. Furthermore, the results of the indirect influence hypothesis test show that leadership style has a significant positive influence on performance through job satisfaction, work discipline has a negative but not significant influence on performance through job satisfaction, and compensation has a negative but not significant influence on performance through job satisfaction.